2001
DOI: 10.1037/0022-3514.80.5.782
|View full text |Cite
|
Sign up to set email alerts
|

Devaluing domains in response to threatening intergroup comparisons: Perceived legitimacy and the status value asymmetry.

Abstract: Group status and status legitimacy were tested as moderators of devaluing in response to threatening intergroup comparisons. In 3 experiments, participants received feedback comparing their in-group (based on school or gender) to a higher or lower status out-group. When the legitimacy of group status differences was assumed (Studies 1 and 2) or manipulated (Study 3), participants devalued the domain when their in-group compared unfavorably with a lower status out-group but did not devalue the domain when their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(88 citation statements)
references
References 41 publications
3
82
0
3
Order By: Relevance
“…Although there has already been some evidence that domains in which low-status groups excel are normally devalued and regarded as providing little utility for gaining status relevant rewards (e.g., Schmader et al, 2001), our argument goes further by positing that…”
Section: Accepted Manuscriptmentioning
confidence: 65%
See 2 more Smart Citations
“…Although there has already been some evidence that domains in which low-status groups excel are normally devalued and regarded as providing little utility for gaining status relevant rewards (e.g., Schmader et al, 2001), our argument goes further by positing that…”
Section: Accepted Manuscriptmentioning
confidence: 65%
“…As a consequence, abilities, skills, or domains in which higher status groups excel are valued, whereas domains in which lower status groups outperform their higher status counterparts are devalued and regarded as having little or no utility in gaining status-relevant rewards (e.g., Schmader, Major, Eccleston, & McCoy, 2001). A consequence of this would be that failure in domains with little utility would be less likely to elicit negative evaluations than failure in high utility domains.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…In this way it was conveyed that the scores of all group members present (including themselves) reflected the intergroup performance difference that was supposedly found in other studies. Personal performance feedback prevented participants from protecting their self-esteem by distancing themselves from low ingroup performance by estimating their personal performance to be higher than the group's performance (Schmader, Major, Eccleston, & McCoy, 2001). …”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have already shown that domains in which higher status groups excel are usually valued highly, whereas domains in which lower status groups excel are devalued and regarded as having no or little utility for gaining status-relevant rewards (e.g., Schmader, Major, Eccleston, & McCoy, 2001). Such an effect would result in stronger effects of success and failure on dimensions in which the high-status group outperforms the low status group.…”
Section: Self-evaluation Self-esteem and Social Identitymentioning
confidence: 98%